The Healthy Lifestyles Programme (HeLP), a novel school-based intervention to prevent obesity in school children: study protocol for a randomised controlled trial - Wyatt, Katrina M (BioMed Central, 2013)
BACKGROUND: Over the last three decades there has been a substantial increase in the proportion of children who are overweight or obese. The Healthy Lifestyles Programme (HeLP) is a novel school-based intervention, using highly interactive and creative delivery methods to prevent obesity in children. METHODS/DESIGN: We describe a cluster randomised controlled trial to evaluate the effectiveness and cost effectiveness of HeLP. The intervention has been developed using intervention mapping (involving extensive stakeholder involvement) and has been guided by the Information, Motivation, Behavioural Skills model. HeLP includes creating a receptive environment, drama activities, goal setting and reinforcement activities and runs over three school terms. Piloting showed that 9 to 10 year olds were the most receptive and participative. This study aims to recruit 1,300 children from 32 schools (over half of which will have ≥19% of pupils eligible for free school meals) from the southwest of England. Participating schools will be randomised to intervention or control groups with baseline measures taken prior to randomisation. The primary outcome is change in body mass index standard deviation score (BMI SDS) at 24 months post baseline. Secondary outcomes include, waist circumference and percent body fat SDS and proportion of children classified as overweight or obese at 18 and 24 months and objectively measured physical activity and food intake at 18 months. Between-group comparisons will be made using random effects regression analysis taking into account the hierarchical nature of the study design. An economic evaluation will estimate the incremental cost-effectiveness of HeLP, compared to control, from the perspective of the National Health Service (NHS)/third party payer. An in-depth process evaluation will provide insight into how HeLP works, and whether there is any differential uptake or engagement with the programme. DISCUSSION: The results of the trial will provide evidence on the effectiveness and cost effectiveness of the Healthy Lifestyles Programme in affecting the weight status of children. TRIAL REGISTRATION: ISRCTN15811706